Body image distortions following spinal cord injury. Issue 2 (1st December 2012) - Fuentes, Christina T; Pazzaglia, Mariella; Longo, Matthew R; Scivoletto, Giorgio; Haggard, Patrick
Abstract : Background: Following spinal cord injury (SCI) or anaesthesia, people may continue to experience feelings of the size, shape and posture of their body, suggesting that the conscious body image is not fully determined by immediate sensory signals. How this body image is affected by changes in sensory inputs from, and motor outputs to, the body remains unclear. Methods: We tested paraplegic and tetraplegic SCI patients on a task that yields quantitative measures of body image. Participants were presented with an anchoring stimulus on a computer screen and told to imagine that the displayed body part was part of a standing mirror image of themselves. They then identified the position on the screen, relative to the anchor, where each of several parts of their body would be located. Veridical body dimensions were identified based on measurements and photographs of participants. Results: Compared with age matched controls, paraplegic and tetraplegic patients alike perceived their torso and limbs as elongated relative to their body width. No effects of lesion level were found. Conclusions: The common distortions in body image across patient groups, despite differing SCI levels, imply that a body image may be maintained despite chronic sensory and motor loss. Systematic alterations in body image follow SCI although our results suggest these may reflect changes in body posture, rather than loss of specific sensorimotor pathways. These findings provide new insight into how the body image is maintained, and may prove useful in treatments that intervene to manipulate the body image.